Subacute sclerosing panencephalitis should be eliminated by measles vaccination - Wei-Liang Liu; Zhi-Xu He; Fang Li; Dian He; Rong Ai (Taylor & Francis Group, 2017)
1 patient with SSPE at 4 y. He had had measles and measles encephalitis at 7.5 months. In China, the first and the second measles immunizations are recommended at 8 months and at 18-24 months, respectively. We recommend above immunizations should be given separately at 6 months and at 12-15 months.